How tall, how short, how faraway - Adler, David A, 1947-; Tobin, Nancy (New York : Holiday House, 1999)
Introduces several measuring systems such as the Egyptian system, the inch-pound system, and the metric system.
Wilson's Children, October 2010.
School Library Journal, April 1999.
Book Links (A.L.A.), June 2010.
Horn Book, March 1999.
Bulletin (Center for Children's books), September 1999.
Kirkus Review, February 1999.
Keywords: Measurement -- Juvenile literature; Measurement; Measurement; Measurement